What about Platelet Function in Platelet Concentrates? - Prudent, Michel (Hämostaseologie, 2020)
The characterization of platelet concentrates (PCs) in transfusion medicine has been performed with different analytical methods and platelet lesions (from biochemistry to cell biology) have been documented. In routine quality assessment and validation of manufacturing processes of PCs for transfusion purposes, only basic parameters are monitored and the platelet functions are not included. However, PCs undergo several manipulations during the processing and the basic parameters do not provide sensitive analyses to properly picture out the impact of the blood component preparation and storage on platelets. To improve the transfusion supply chain and the platelet functionalities, additional parameters should be used. The present short review will focus on the different techniques to monitor ex vivo platelet lesions from phenotype characterization to advanced omic analyses. Then, the opportunities to use these methods in quality control, process validation, development, and research will be discussed. Functional markers should be considered because they would be an advantage for the future developments in transfusion medicine.
Keywords: monitoring; platelet; quality control; transfusion medicine